Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.4049/jimmunol.1203062
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of CD99 with Its Paralog CD99L2 Positively Regulates CD99L2 Trafficking to Cell Surfaces

Abstract: Mouse CD99 and its paralog CD99-like 2 (CD99L2) are surface proteins implicated in cellular adhesion and migration. Although their distributions overlap in a wide variety of cells, their physical/functional relationship is currently unknown. In this study, we show the interaction between the two molecules and its consequence for membrane trafficking of mouse (m)CD99L2. The interaction was analyzed by bimolecular fluorescence complementation, immunoprecipitation, and fluorescence resonance energy transfer assay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…It is known that PILR family members interact with CD99 ( Kogure et al, 2011 ; Lee et al, 2012 ; Nam et al, 2013 ; Sun et al, 2012 ; Tabata et al, 2008 ). As we have reported before, CD99 activation with monoclonal antibody recruited SHP2 and allowed it to dephosphorylate FAK at Y397 to regulate the FA complex, resulting in a decrease in β1 integrin activity ( Lee et al, 2012 ; 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…It is known that PILR family members interact with CD99 ( Kogure et al, 2011 ; Lee et al, 2012 ; Nam et al, 2013 ; Sun et al, 2012 ; Tabata et al, 2008 ). As we have reported before, CD99 activation with monoclonal antibody recruited SHP2 and allowed it to dephosphorylate FAK at Y397 to regulate the FA complex, resulting in a decrease in β1 integrin activity ( Lee et al, 2012 ; 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…CD99 does not increase to compensate for absence of CD99L2. A recent paper by Nam et al (Nam et al, 2013) showed that in mouse cells CD99 and CD99L2 interact via their cytoplasmic domains during their biosynthesis. CD99 helps CD99L2 get to the cell surface, and levels of CD99L2 were decreased in cells lacking CD99.…”
Section: Discussionmentioning
confidence: 99%
“…CD99 facilitates TEM through homophilic interactions between the two cell types [108]. Similarly, CD99L2 has been reported to function through homophilic interactions but it may have another unidentified ligand [109111]. Disruption of CD99 and CD99L2 interactions using function blocking antibodies or genetic knock out (in the case of CD99L2) impairs leukocyte extravasation in vitro and in vivo.…”
Section: The Molecules Involved On the Endothelial Cellmentioning
confidence: 99%
“…Interestingly though, in a study using the mouse homologues of CD99 and CD99L2, Nam and coworkers showed that the two molecules interact with each other heterophilically through their cytoplasmic tails [111]. Through this interaction CD99 appears to facilitate the trafficking of CD99L2 to the plasma membrane.…”
Section: The Molecules Involved On the Endothelial Cellmentioning
confidence: 99%